Comprehensive compositional assessment of bioactive compounds in diverse pea accessions. (March 2023) - Han, Xiumei; Akhov, Leonid; Ashe, Paula; Lewis, Courteney; Deibert, Leah; Irina Zaharia, L.; Forseille, Lily; Xiang, Daoquan; Datla, Raju; Nosworthy, Matthew; Henry, Carol; Zou, Jitao; et al.
Graphical abstract: Highlights: Wide diversity of profiles of bioactive compounds present in pea accessions. An improved method for simultaneous detection of multiple phytoestrogens. Developed method for direct analysis of isoflavones in their natural forms. Isoliquiritigenin is the predominant phytoestrogen in the analyzed accessions. Providing an immense resource for pea research community and breeding. Abstract: Pea ( Pisum sativum L.) is an important legume crop providing a good source of protein, vitamins, minerals and bioactive compounds with health benefits for humans. In this study, an improved method for simultaneous analysis of multiple phytoestrogens among 100 pea accessions was developed. Ipriflavone, (a synthetic isoflavone), was used as an internal standard for the semiquantitative analysis of 17 phytoestrogens including isoflavone aglycones and conjugates, allowing direct analysis of isoflavones in their naturally occurring forms. This comprehensive dataset demonstrated that the isoflavones varied greatly and some accessions tended to have high levels of multiple phytoestrogens among the 100 accessions analyzed. Isoliquiritigenin followed by glycitein were the predominant compounds detected in the accessions and showed the highest correlation with the total phytoestrogens content. Secoisolariciresinol content was consistently higher in yellow cotyledon peas than in green cotyledon peas, whereas the contents of coumestrol, genestein and secoisolariciresinol were significantly correlated with seed coat color. The total phenolics and saponins showed a wide range of variability among the accessions with higher concentrations of total phenolics observed in seeds with pigmented seed coat or yellow cotyledon seeds, suggesting the synthesis of saponins and phenolics are significantly affected by metabolic pathway genes controlling cotyledon color or seed coat color. This study profiled the variability of bioactive compounds of pea seed quality traits in diverse pea accessions and provides an immense resource for continued research, breeding and selection of genotypes for a wide range of applications.